Efektivitas Brotowali (Tinospora Crispa) Sebagai Alternatif Terapi Diabetes Melitus: Tinjauan Literatur 2020-2025: Penelitian - Sari, Ratih Indah; Yuvita, Yuvita; Apriani, Dwi Wulan (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia resulting from impaired insulin secretion or action. Among various herbal remedies employed as alternative therapies for diabetes, Tinospora crispa, commonly known as brotowali, has attracted considerable scientific interest. This traditional medicinal plant exhibits antidiabetic potential due to its rich content of bioactive compounds such as flavonoids, alkaloids, and terpenoid glycosides. This literature review aims to evaluate recent studies investigating the antidiabetic activity of T. crispa. The review analyzed eight scientific articles published between 2020 and 2025 that met specific inclusion criteria. The findings reveal that T. crispa lowers blood glucose levels, enhances insulin secretion, promotes pancreatic β-cell regeneration, and inhibits α-glucosidase enzyme activity. These therapeutic effects are further potentiated when T. crispa is combined with other medicinal plants. However, several studies also report potential renal. phytotherapeutic agent for diabetes, although further research is necessary to establish its safety and clinical efficacy.